TOURISM BROKERS' PERSPECTIVE ON TURKEY'S IMAGE: MARKETING COMMUNICATIONS AND SUBJECTIVE NORMS AS MEDIATORS - Mohammad Najjarzadeh; Nazanin Amirzade; Mohammade Reza Asadi Zarch (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
There is growing investment in the tourism industry, especially in the countries with potential attractions. All tourism destinations attempt to compete with other opponents and be distinctive. They also try to provide more particular experiences for visitors. The present study aims to investigate the effectiveness of the tourism brokers’ perspective on Turkey's image as a tourism destination through the mediating role of marketing communications and subjective norms. This study is an applied research based on descriptive correlational studies. The research population includes all the tourism brokers in Iran (travel agencies, tour operators, and travel agents) who provide outgoing Turkey tours. The samples (including 250 tourism brokers) are selected using a convenience sampling method and data were collected by using a questionnaire. To analyze data, Structural Equation Modeling (SEM) is applied using the Smart PLS 3 software. Results show that cognitive and affective images have a significant direct effect on tourism destination image while they have a significant indirect effect on destination image through the mediating role of marketing communications and subjective norms. Marketing Communications and Subjective Norms have a significant direct effect on destination image. Previously, there were not adequate information on and attention to the factors affecting tourism brokers in promoting Turkey as a cross-border destination, so this study is conducted to present new ideas for marketers and tourism brokers.